2020
DOI: 10.1177/0361198120975414
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting the Interlayer Shear Strength of Laboratory and Field Samples

Abstract: Asphalt emulsion is the most widely used tack coat material in the U.S. The objective of this study is to investigate factors that may affect the interlayer bond shear strength of asphalt emulsion tack coats of both laboratory and field compacted samples. The laboratory study included six types of tack coat materials applied on two surfaces with two residual application rates. The field study phase involved validation of the interlayer shear performance findings using field cores extracted from paving projects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Researchers, ( 8 , 11 , 13 , 19 ) have found that an increased application rate of tack coat materials generally results in higher bond strength up to an optimum rate, after which higher dosage is detrimental. Surface texture has an influence on the bond strength ( 20 ). Bond strength increases over time after construction for emulsion tack coat materials ( 11 , 13 , 14 , 21 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Researchers, ( 8 , 11 , 13 , 19 ) have found that an increased application rate of tack coat materials generally results in higher bond strength up to an optimum rate, after which higher dosage is detrimental. Surface texture has an influence on the bond strength ( 20 ). Bond strength increases over time after construction for emulsion tack coat materials ( 11 , 13 , 14 , 21 ).…”
Section: Literature Reviewmentioning
confidence: 99%